Stylistic Metaphor: Senses Of Sight And Smell In The Works Of Martin Luther King Junior. And Bate Besong - Fomukong, Seino Evangeline Agwa (Advances in Social Sciences Research Journal, 2017)
Stylisticians analyse texts looking at how language affects readers. This implies that the writer or the speaker of a text takes into account the choice of language, that is, what will affect the reader or listener in the way the writer or speaker wants. They intent of the writer or speaker may come with images that are trigged off by language through which they recall or evoke instances of physical sensual perception. Martin Luther King Junior and Bate Besong are authors who make use of the sensual perception of darkness and stench, respectively in their works. The study using the Dual Coding Theory and Conceptual Metaphor Theory concludes that racial discrimination is darkness and any social ill is stench.